Patriot Acts - Platt, Anthony M. (Social justice, 2003)
Part of a special issue on race, security, and social activism in the U.S. Changes in the repressive state apparatus since the terrorist attacks of September 11, 2001, are discussed. The cultural expressions of patriotism that both inform and justify the roll back of the reforms that took place after Watergate and the chilling of civil liberties are explored. In addition, the repercussions of the 2001 Patriot Act, the related changes in policy and government, and the rise of right-wing nationalism are examined.